2015
DOI: 10.7314/apjcp.2014.15.23.10175
|View full text |Cite
|
Sign up to set email alerts
|

The RTEL1 rs6010620 Polymorphism and Glioma Risk: a Meta-analysis Based on 12 Case-control Studies

Abstract: Background: The association between the RTEL1 rs6010620 single nucleotide polymorphism (SNP) and glioma risk has been extensively studied. However, the results remain inconclusive. To further examine this association, we performed a meta-analysis. Materials and Methods: A computerized search of the PubMed and Embase databases for publications regarding the RTEL1 rs6010620 polymorphism and glioma cancer risk was performed. Genotype data were analyzed in a meta-analysis. Odds ratios (ORs) with 95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Therefore, loss of RTEL1 function induces shortening of telomeres and chromosomal breaks. Helicase is a key protein in the repair of single-strand breaks, by direct involvement in the repair (DSB) of the English double-strand break (Du et al, 2014). However, in this study the RTEL1-rs6010620 polymorphism showed no association with gliomas, corroborating a study in North American cases (Lee et al, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, loss of RTEL1 function induces shortening of telomeres and chromosomal breaks. Helicase is a key protein in the repair of single-strand breaks, by direct involvement in the repair (DSB) of the English double-strand break (Du et al, 2014). However, in this study the RTEL1-rs6010620 polymorphism showed no association with gliomas, corroborating a study in North American cases (Lee et al, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…The age, gender, extent of resection, radiotherapy, chemotherapy, and histological grade, tumor size and range have been identified as potential contributors to the prognosis of glioma patients (Hayashi et al ., 2017; Guo et al ., 2019). Moreover, many genetic polymorphisms have been identified to be associated with the susceptibility to gliomas and as well as the prognosis of glioma patients (Li et al ., 2013; Du et al ., 2014; Jin et al ., 2016). Therefore, it is critical to identify new glioma therapeutic targets and new diagnostic and prognostic biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The age, gender, extent of resection, radiotherapy, chemotherapy, and histological grade, tumor size and range have been identified as potential contributors to the prognosis of glioma patients [5,6]. Moreover, many genetic polymorphisms have been identified to be associated with the susceptibility to gliomas and as well as the prognosis of glioma patients [7][8][9]. Therefore, it is critical to identify new glioma therapeutic targets and new diagnostic and prognostic biomarkers.…”
Section: Introductionmentioning
confidence: 99%